Pengaruh Fasilitas dan Kualitas Pelayanan Terhadap Kepuasan Wisatawan di The Sila’s Agrotourism Tabanan Bali - Putra, I Kadek Dwipa Riana; Sulastri, Ida Ayu Putu (Jurnal Mosaik Hospitaliti, 2023)
This study aims to (1) determine the effect of facilities on customer satisfaction at The Sila's Agrotourism Tabanan, Bali; (2) determine the effect of service quality on customer satisfaction at The Sila's Agrotourism Tabanan, Bali; and (3) knowing the effect of Facilities and Service Quality on customer satisfaction at The Sila's Agrotourism Tabanan, Bali. This study uses a sample of 75 samples consisting of 6 facilities indicators (X1), 5 service quality indicators (X2), and 4 satisfaction indicators (Y). The research data analysis method uses t-test analysis and multiple regression tests. The results of the analysis of the influence of facilities (X1) on customer satisfaction (Y) in Table 4.9 show a significance level of t of 0.000 which is smaller than = 0.05. In addition, the facility regression coefficient (X1) of 0.000 indicates a positive influence of the facility on customer satisfaction. The results of the analysis of the effect of service quality (X2) on customer satisfaction (Y) in Table 4.9 show a significance level of t of 0.033 which is smaller than = 0.05. In addition, the facility regression coefficient (X1) of 0.033 indicates a positive influence of service quality on customer satisfaction. The results of F arithmetic (14.979) > F table (3.150) This means that there is an increase in facilities and service quality simultaneously which will later be able to increase customer satisfaction at The Sila's Agrotourism, Tabanan.